An Ultrahigh‐Field‐Tailored T1–T2 Dual‐Mode MRI Contrast Agent for High‐Performance Vascular Imaging. Issue 2 (2nd December 2020) - Wang, Jin; Jia, Yinhang; Wang, Qiyue; Liang, Zeyu; Han, Guangxu; Wang, Zejun; Lee, Jiyoung; Zhao, Meng; Li, Fangyuan; Bai, Ruiliang; Ling, Daishun
Abstract: The assessment of vascular anatomy and functions using magnetic resonance imaging (MRI) is critical for medical diagnosis, whereas the commonly used low‐field MRI system (≤3 T) suffers from low spatial resolution. Ultrahigh field (UHF) MRI (≥7 T), with significantly improved resolution and signal‐to‐noise ratio, shows great potential to provide high‐resolution vasculature images. However, practical applications of UHF MRI technology for vascular imaging are currently limited by the low sensitivity and accuracy of single‐mode ( T 1 or T 2 ) contrast agents. Herein, a UHF‐tailored T 1 – T 2 dual‐mode iron oxide nanoparticle‐based contrast agent (UDIOC) with extremely small core size and ultracompact hydrophilic surface modification, exhibiting dually enhanced T 1 – T 2 contrast effect under the 7 T magnetic field, is reported. The UDIOC enables clear visualization of microvasculature as small as ≈140 µm in diameter under UHF MRI, extending the detection limit of the 7 T MR angiography. Moreover, by virtue of high‐resolution UHF MRI and a simple double‐checking process, UDIOC‐based dual‐mode dynamic contrast‐enhanced MRI is successfully applied to detect tumor vascular permeability with extremely high sensitivity and accuracy, providing a novel paradigm for the precise medical diagnosis of vascular‐related diseases. Abstract : An ultrahigh magnetic field (UHF)‐tailored T 1 – T 2 dual‐mode iron oxide nanoparticle‐based contrast agent (UDIOC) with a near‐paramagnetic core and ultracompact hydrophilic surface modification is developed, which exhibits a dually enhanced T 1 – T 2 contrast effect under UHF. By virtue of high‐resolution UHF magnetic resonance imaging (MRI) and a simple double‐checking process, UDIOC‐based dual‐mode imaging enables the assessment of the vascular anatomy and functions with high sensitivity and accuracy.